Measuring Inequality of Opportunity with Imperfect Data : The Case of Turkey - Ferreira, Francisco H.G.; Gignoux, Jeremie; Aran, Meltem (World Bank, Washington, DC, 2014)
The measurement of inequality of opportunity has hitherto not been attempted in a number of countries because of data limitations. This paper proposes two alternative approaches to circumventing the missing data problems in countries where a demographic and health survey and an ancillary household expenditure survey are available. One method relies only on the demographic and health survey, and constructs a wealth index as a measure of economic advantage. The alternative method imputes consumption from the ancillary survey into the demographic and health survey. In both cases, the between-type share of overall inequality is computed as a lower bound estimator of inequality of opportunity. Parametric and non-parametric estimates are calculated for both methods, and the parametric approach is shown to yield preferable lower-bound measures. In an application to the sample of ever-married women aged 30-49 in Turkey, inequality of opportunity accounts for at least 26 percent (31 percent) of overall inequality in imputed consumption (the wealth index).